2007
DOI: 10.1021/la7013754
|View full text |Cite
|
Sign up to set email alerts
|

Cell Dynamics Simulation of Droplet and Bridge Formation within Striped Nanocapillaries

Abstract: The kinetics of droplet and bridge formation within striped nano-capillaries is studied when the wetting film grows via interface-limited growth. The phenomenological time-dependent Ginzburg-Landau (TDGL)-type model with thermal noise is used and numerically solved using the cell dynamics method.The model is two-dimensional and consists of undersaturated vapor confined within a nano-capillary made of two infinitely wide flat substrates. The surface of the substrate is chemically heterogeneous with a single str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It follows that capillary bridges expanding between homogeneous and heterogeneous surfaces fundamentally behave differently. Indeed, the behavior of nanoscale capillary bridges expanding between patchy surfaces (with commensurate nanoscale dimensions) remains practically unexplored (e.g., see refs ). It remains unclear what kind of interactions capillary bridges can induce between patchy surfaces, or how the geometrical and thermodynamic properties of such capillary bridges may vary with the separation between the walls.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that capillary bridges expanding between homogeneous and heterogeneous surfaces fundamentally behave differently. Indeed, the behavior of nanoscale capillary bridges expanding between patchy surfaces (with commensurate nanoscale dimensions) remains practically unexplored (e.g., see refs ). It remains unclear what kind of interactions capillary bridges can induce between patchy surfaces, or how the geometrical and thermodynamic properties of such capillary bridges may vary with the separation between the walls.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of nanoscale WCB confined by chemically heterogeneous surfaces are challenging to predict theoretically. [17][18][19] Understanding how the surface patch geometry affects the properties of capillary bridges can help engineers to design heterogeneous surfaces to improve chip selfalignment during pickup for the fabrication of chip arrays, [20] and micro-transfer process in printing process. [21,22] In a recent molecular dynamics simulations study, we [13] showed that the properties of a translationally-symmetric (TS) nanoscale WCB formed between two flat surfaces with a stripe-like hydrophilic patch can be described remarkably well by capillary theory.…”
Section: Introductionmentioning
confidence: 99%
“…Various numerical methods such as the Monte Carlo 33 , the molecular dynamics 34 and the lattice Boltzmann method 35 have been developed to study the dynamic of cavity or bubble formation and the evaporation. Recently, we have developed a numerical method based on the time dependent Ginzburg-Landau model combined with the cell dynamics method to study the dynamics of nucleation in various situations 36,37 . It will be interesting to use this cell dynamics method to study the dynamics of cavity or bubble formation.…”
Section: Discussionmentioning
confidence: 99%